Development and initial evaluation of the usefulness of a question prompt list to promote patients' level of information about work-related medical rehabilitation: a pilot study - Lukasczik, Matthias; Wolf, Hans Dieter; Vogel, Heiner (Frontiers in Rehabilitation Sciences, 2024)
Background: The purpose of this study was to develop a question prompt list (QPL) to support patients undergoing work-related medical rehabilitation in obtaining relevant information and to explore how patients and physicians rate the QPL regarding its usefulness, practicability, and perceived (additional) effort.Methods: An initial item pool was assessed by rehabilitation patients (N=3) in cognitive interviews, rated by physicians and other health professionals (N=11), and then further modified.The final QPL version (16 items) was used by patients (N=36) in medical admission interviews in an inpatient medical rehabilitation facility and then evaluated. Physicians evaluated the QPL after each interview with a study participant (N=6; k=39 interviews).The QPL was used by 50% of patients who rated its usefulness and comprehensibility positively. Neither the need for information nor satisfaction with the information received was correlated with QPL use. The physicians' assessment showed a positive evaluation regarding the provision of information and structuring of the conversation, but also a higher perceived time expenditure.Conclusions: While initial testing of the QPL in work-related medical rehabilitation as a tool to support patient-provider communication generally showed a favorable evaluation by patients using it and physicians, future research should address its validity and effectiveness.Patient or public contribution: Rehabilitation patients were included in the development (cognitive interviews) and the evaluation of the instrument.